DETERMINAN AGRESIVITAS PAJAK PERUSAHAAN MANUFAKTUR SEBELUM MASA PANDEMI DI BURSA EFEK INDONESIA PERIODE 2017 – 2019 - Ari Hadi Prasetyo; Amelia Sandra Sandra; Rizka Indri Afrianti; Yustina Triyani Triyani; Angelica Gavra Limarga (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The difference in perspective on taxes between the government and company managers who consider taxes is a burden that reduces company profits which has an impact on reducing the prosperity of companies and managers as agents, while on the state side taxes are as a function of the budget for state management. This difference in interests encourages managers to take tax aggressiveness to reduce the tax burden. This study aims to determine the factors that can encourage tax aggressiveness, including Profitability, Company Size, Leverage, Capital Intensity and Independent Commissioners. With a population of all manufacturing companies listed on the Indonesia Stock Exchange prior to the Covid-19 pandemic for the 2017-2019 period, using the Non-Probability Sampling technique, using the purposive sampling method. Data analysis used was data pooling test, descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the variable company size has sufficient evidence of a significant positive effect on tax aggressiveness and the independent commissioner variable has sufficient evidence of a significant negative effect on tax aggressiveness, while the variables of Profitability, Leverage and Capital Intensity have insufficient evidence of a significant effect on tax aggressiveness.